Coalition and Opposition in the Perspective of Islamic Party Elites in Lampung: A Maslahah Based Analysis - Hawari, Nadirsah; Agustam; Abdul Halim (JURNAL TAPIS, 2025)
This study seeks to answer a central question concerning the moral and ethical boundaries for political parties that supported losing candidates in determining whether to join the ruling coalition or remain in opposition particularly when they had previously taken a strong stance against the candidate who is now in power. The discourse on coalition and opposition has been resurfaced and is frequently associated with ethical considerations in political practice. Parties that choose to join the government generally justify their decision based on maslahah murlahan as a means of promoting public welfare, while those that remain in opposition view the maintenance of checks and balances as another form of maslahat that must be upheld. This research employs a qualitative approach with a descriptive-analytic character, using a maslahat-weighing framework based on the perspectives of Islamic party elites in Lampung Province. Primary data were obtained through in-depth interviews with six informants, namely provincial-level elites from the NasDem Party, PKB, and PKS. Secondary data were collected from documents, classical fiqh and ulus fiqh literature, and Islamic political studies. Data analysis was conducted through stages of data reduction, thematic categorization, data presentation, and inductive conclusion drawing. The findings reveal that both coalition and opposition represent legitimate political choices within a democratic system and are equally grounded in pragmatics as well as benefit considerations. Their distinction lies in the moral boundaries and social propriety aimed at public interest. Therefore, it is acceptable for coalition parties to occasionally reject government policies if they are deemed inconsistent with public benefit, just as opposition parties are not obliged to reject every outright government policy.